German practice in international law 2020 Volume 2 - Talmon, Stefan 1965- (Cambridge University Press, 2023)
Customary international law is based on State practice. This book presents the international law practice of Germany, the world's fourth-largest economy and powerhouse of the European Union, which makes an important contribution to the creation and development of customary international law. It is the first and only presentation of German practice in international law in English. The book combines a case study approach, providing analysis and commentary on Germany's practice, with a classic digest of primary materials, including diplomatic correspondence, statements, and court decisions. The book is an ideal complement to other compilations of international law practice and is an essential resource for scholars and practitioners of international law. It will also be of interest to scholars of international relations, politics, and diplomatic studies
Title from publisher's bibliographic system (viewed on 09 Feb 2023)
Foundations and functions of international law -- States and their organs -- Inter-state political and economic relations and transactions -- State jurisdiction and immunities -- State responsibility and liability -- Antarctica, sea, air and space -- Individuals, their human rights and their international criminal responsibility -- Natural resources and the environment -- The United Nations and other international organisations -- Use of force, arms control, and disarmament -- International disputes and their settlement
Keywords: International law / Germany; International and municipal law / Germany